2009
DOI: 10.1097/ccm.0b013e3181a00578
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing the pediatric intensive care unit: Perspective from parents of children with severe antecedent disabilities*

Abstract: Children with severe antecedent disabilities and their parents are inextricably linked with critical care services. Study results provide data that can be used to help clinicians better understand the perspectives of these parents and also help guide interventions to improve care and support. Although communication is essential, the structure and processes of critical care including rounding format, continuity in management, and mutual participation models should be tested and tailored to better meet parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 43 publications
1
95
0
4
Order By: Relevance
“…Nurses caring for this growing population of children must be adept at providing care to patients with complex conditions and a high level of technology dependence, but they must also have the ability to work with families who face a unique and often ongoing set of challenges. These families often present to the PICU with expertise in caring for their child, and they want that expertise to be honored and valued (Graham, Pemstein, & Curley, 2009; Reeves, Timmons, & Dampier, 2006), something best done by a set of caregivers who can provide consistent care. Additionally, these families are often in the PICU because of a health crisis that may represent a worsening of their child’s condition, and they are likely to be dealing with the grief and loss associated with such an event.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses caring for this growing population of children must be adept at providing care to patients with complex conditions and a high level of technology dependence, but they must also have the ability to work with families who face a unique and often ongoing set of challenges. These families often present to the PICU with expertise in caring for their child, and they want that expertise to be honored and valued (Graham, Pemstein, & Curley, 2009; Reeves, Timmons, & Dampier, 2006), something best done by a set of caregivers who can provide consistent care. Additionally, these families are often in the PICU because of a health crisis that may represent a worsening of their child’s condition, and they are likely to be dealing with the grief and loss associated with such an event.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, parents want to share their specialist knowledge of the child, 45,53 including cues and indicators of pain, 44,52 and physical, emotional and spiritual needs. 47 Yet some parents report that their medical knowledge is often either not solicited or disregarded, 38,62 and their questions and concerns are left unaddressed. 39,52,55 A study by de Vos et al 37 found that only a third of clinicians invited families to share their observations about the child’s ability to interact or their perceptions of the child’s level of comfort.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
“…The number of interviews, although small, is similar to the number typically needed to reach thematic saturation in other qualitative studies. 22,23 Future directions of our research will entail different study designs, such as interviewing the parents immediately after the delivery of bad news, using interviewers and coders who do not normally work in the medical field to minimize professional bias coming from having been the bearer of bad news in the past, or designing multi-institution studies to have different cultural and institutional backgrounds represented, as well as a vast array of different medical conditions in different stages of the disease process.…”
Section: Discussionmentioning
confidence: 99%